Chronic kidney disease in type 2 diabetes: pathology - Thomas, Merlin (Henry Stewart Talks, 2023)
Changes in diabetic kidney disease, Glomerular hypertrophy, Mesangial expansion, Thickening of the GBM involves podocyte de-differentiation, Thickening of Bowman’s capsule, Glomerular sclerosis, Arteriolar hyalinosis, Tubulointerstitial fibrosis, CDK and increased mortality